IGR J12580+0134: The Nearest Tidal Disruption Event and Its Faint Resurrection - A. Danehkar (The Astrophysical Journal)
Tidal disruption events (TDEs) are X-ray and gamma-ray radiations emerging from the tidal disintegration of a star or substellar object that passes too close to a supermassive black hole (SMBH) at the center of a galaxy. In 2010 November, a TDE designated as IGR J12580+0134 occurred in the galaxy NGC 4845, and it was traced by follow-up XMM-Newton observations in 2011 January. To identify a further TDE based on the radio outburst cycle, we requested NICER monitoring observations for nearly 1 yr beginning in 2023 March, which we studied here along with the previous XMM-Newton observations. We analyzed X-ray brightness changes using hardness analysis and principal component analysis (PCA) and conducted spectral analysis of the source continuum. The NICER observations revealed the presence of some X-ray flares during 2023 March–June that were much fainter than the TDE observed using XMM-Newton in 2011. The PCA component that mainly contributes to the X-ray outbursts during the TDE is a heavily absorbed power-law continuum emission, whereas there is a small contribution from collisionally ionized plasma in the soft excess, likely from a colliding wind or jet. Similarly, the PCA of the NICER data relates the X-ray flares to a power-law spectrum, albeit with a much lower absorbing column, and partially to soft collisional plasma. The faint X-ray flares captured by NICER could be associated with extremely weak accretion onto the SMBH resident in this galaxy and thus potentially a low-luminosity active galactic nucleus.